Mammalian Target of Rapamycin Pathway Regulates Insulin Signaling via Subcellular Redistribution of Insulin Receptor Substrate 1 and Integrates Nutritional Signals and Metabolic Signals of Insulin - Takano, Atsuko (American Society for Microbiology, 2001)
A pathway sensitive to rapamycin, a selective inhibitor of mammalian target of rapamycin (mTOR), down-regulates effects of insulin such as activation of Akt (protein kinase B) via proteasomal degradation of insulin receptor substrate 1 (IRS-1). We report here that the pathway also plays an important role in insulin-induced subcellular redistribution of IRS-1 from the low-density microsomes (LDM) to the cytosol. After prolonged insulin stimulation, inhibition of the redistribution of IRS-1 by rapamycin resulted in increased levels of IRS-1 and the associated phosphatidylinositol (PI) 3-kinase in both the LDM and cytosol, whereas the proteasome inhibitor lactacystin increased the levels only in the cytosol. Since rapamycin but not lactacystin enhances insulin-stimulated 2-deoxyglucose (2-DOG) uptake, IRS-1-associated PI 3-kinase localized at the LDM was suggested to be important in the regulation of glucose transport. The amino acid deprivation attenuated and the amino acid excess enhanced insulin-induced Ser/Thr phosphorylation and subcellular redistribution and degradation of IRS-1 in parallel with the effects on phosphorylation of p70 S6 kinase and 4E-BP1. Accordingly, the amino acid deprivation increased and the amino acid excess decreased insulin-stimulated activation of Akt and 2-DOG uptake. Furthermore, 2-DOG uptake was affected by amino acid availability even when the degradation of IRS-1 was inhibited by lactacystin. We propose that subcellular redistribution of IRS-1, regulated by the mTOR-dependent pathway, facilitates proteasomal degradation of IRS-1, thereby down-regulating Akt, and that the pathway also negatively regulates insulin-stimulated glucose transport, probably through the redistribution of IRS-1. This work identifies a novel function of mTOR that integrates nutritional signals and metabolic signals of insulin.